Puerto rosario consolida su inserción en la región y en el sistema portuario nacional - Raposo, Isabel María (2019)
The port of Rosario exhibits great potential, being a reference of a port region that acquires marked specialization over the time, with important links with the territory and very accessible to different productions of the regional economies in the country. The present expectations are confronted with the strong dynamics of change and alterations in the flow of foreign trade, added with instability at the global level. New actors, delayed investments, conflicts between system actors and regulatory problems, add uncertainty in the insertion of the port into the regional and national scheme.